URGENSI PEMBELAJARAN ABAD 21 MODEL PEMBELAJARAN BERBASIS INKUIRI: TINJAUAN PUSTAKA - Fitriani, Riska; Asyhar, Rayandra; Hariyadi, Bambang; Hasibuan, Haris Effendi; Javed, Muhammad Ahmad (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
Education today has led to the importance of 21st century learning. The 21st century directs life to four pillars, namely learning to know, learning to do, learning to be and learning to live together. The four pillars contain specific skills to be developed in the learning process such as communication skills, critical thinking, collaboration, creation and innovation, information literacy, and problem solving. This study reviews the importance of the role of 21st century learning in the inquiry based learning model as a learning model that can solve the challenges of the 21st century. Based on the results of the analysis of the articles on the inquiry based learning model, it was found that the inquiry based learning model is one of the learning models that can be used in the 21st century to guide students to achieve the four skills in the 21st century. The inquiry learning model is a learning model that prepares students in situations to conduct their own experiments so that they can think critically to seek and find answers to a questionable problem. Inquiry allows students to have free space for students to learn, but provides clear boundaries of exploration.